2007
DOI: 10.1088/0026-1394/44/4/s03
|View full text |Cite
|
Sign up to set email alerts
|

Methods for primary standardization of activity

Abstract: A succinct overview is presented of primary standardization methods for activity. They have been subdivided into high-geometry (4π or 2π ) methods, defined-solid-angle counting methods and coincidence counting methods. References are provided of work explaining the basics of the methods as well as papers describing recent developments and applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 160 publications
1
55
0
2
Order By: Relevance
“…A small linear correction was applied to the dataset to compensate for increasing colour quenching in the scintillation cocktail with time. Since the TDCR method (Broda, Cassette, and Kossert, 2007; is a primary standardisation technique for radioactivity (Pommé, 2007), the PTB decay-rate measurements showed a far higher stability (∼ 10 −4 ) than the BNL gas-flow proportional counter measurements (∼ 10 −3 ) on which Sturrock et al have based their claims.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small linear correction was applied to the dataset to compensate for increasing colour quenching in the scintillation cocktail with time. Since the TDCR method (Broda, Cassette, and Kossert, 2007; is a primary standardisation technique for radioactivity (Pommé, 2007), the PTB decay-rate measurements showed a far higher stability (∼ 10 −4 ) than the BNL gas-flow proportional counter measurements (∼ 10 −3 ) on which Sturrock et al have based their claims.…”
Section: Measurementsmentioning
confidence: 99%
“…In particular, they observed a prominent 'transient cycle' of 12.7 a −1 (28.76 days period, 0.07% amplitude) in spectrograms formed from countings of 36 Cl and 32 Si decays in a gasflow proportional counter at BNL (Alburger, Harbottle, and Norton, 1986) and found them indicative of the synodic rotation rate of the radiative zone of the Sun, since it matches its helioseismologically determined period of 28.7 days (Schou et al, 1998;Komm et al, 2003). However, it is questionable whether all experimental uncertainties were under control in the aforementioned 36 Cl and 32 Si decay measurements (Pommé, 2015(Pommé, , 2016. Scargle (2016, 2017) also linked the 12.7 a −1 period with an insignificantly small oscillation in the Super-Kamiokande (SK-I) (Yoo et al, 2003) neutrino flux measurements and concluded that modulations in 'neutrino-induced' beta decays can provide information about the deep solar interior.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this belief is unknown to the original authors of the work; (3) The 2007 article by Collé et al [7] did not refer to the fitted value of 128.3 a as a half-life determination (clearly insisting that it was not), and never claimed that the reported fitting uncertainty of 7 a was an uncertainty on the half-life; (4) The ''robustness'', dependent on the 209 Po solution stability, and the ''trueness and repeatability'' of the LS spectrometry was treated in extenso in the Collé et al articles [6,7,15], while the PSB authors largely neglected to appreciate the rigor employed to ensure that ''the measurement method and data analyses used the identical protocols in all cases'' [7,15]; and (5) The NIST measurement methodology for the half-life determination was based on a unique LS spectral analysis procedure that is specific for the case of 209 Po decay (to account for the delayed 2-keV isomeric transition in 205 Pb and for the radiations accompanying the 0.45 % electron-capture branch to 209 Bi), and had absolutely no relation or relevance to the two references (Broda [21] and Pommé [22] ) cited in PSB. The PSB authors could have more usefully directed readers to any one of the three publications [6,7,15] (and even a pending one [16] referenced in [15] ) that describes the measurement method in great detail.…”
Section: Resultsmentioning
confidence: 99%
“…But to use this type of detectors in gamma spectrometry, it is necessary to know efficiencies and resolution of well type detector as function of gamma energy and also variation of the detector crystal efficiency as a function of the well depth (Mannhart and Vonach, 1978;Brinkman et al, 1963;Cejnar and Kovar, 1979). Also the self absorption of gamma rays by the sample would reduce the effective efficiency of the measuring system (Pommé, 2012(Pommé, , 2007Akar Tarim et al, 2012). In this paper, values of the well type 9 in.x9 in.…”
Section: Introductionmentioning
confidence: 99%